Lead Contamination of Surgical Gloves by Contact with a Lead Hand. (19th June 2011) - Mehra, A.; Deakin, D. E.; Khan, A.; Sheehan, T. M. T.; Nightingale, P.; Deshmukh, S. C.
Abstract : Background . "Lead hands" are frequently used to maintain hand and finger position in hand surgery. The malleability and strength of lead make it ideal for this purpose. The aim of this study was to determine the amount of lead transferred to a surgeon's glove during handling of a lead hand. Method . Sterile surgical gloves were wiped over the surface of a lead hand. The number of wipes was varied, the gloves were then sent to a trace elements laboratory, and the lead content transferred to each glove was determined. Results . The amount of lead transferred to each glove increased with increasing exposure to the lead hand. After twenty wipes, up to 2 mg of lead was transferred to the surgeon's glove. Covering the lead hand with a sterile drape markedly reduced the lead transferred to the surgeon's glove. Conclusion . Significant amount of lead is transferred on to the gloves after handling a lead hand. This risks wound contamination and a foreign body reaction. Covering the lead hand with a sterile drape may minimise the risk of surgical wound contamination.